Septic Shock Immediately following Percutaneous Suprapubic Catheterization - Cale E. Leeson; Brianna-Lee Beaudry; Geoffrey R. Wignall (Case Reports in Urology)
Suprapubic catheterization (SPC) is considered a safe and effective procedure for long-term bladder decompression. With proper technique and appropriate patient selection, significant complications of SPC are rare. Immediate postoperative septic shock (i.e., within the first 24 hours of surgery) is rarely reported. We report a case of an 83-year-old patient who developed septic shock within one hour of suprapubic catheterization for a chronic hypotonic bladder, highlighting the importance of early recognition of complications from SPC and prompt management to ensure positive outcomes.